Neuropeptide F signaling regulates parasitoid-specific germline development and egg-laying in Drosophila. - Madhumala K Sadanandappa; Shivaprasad H Sathyanarayana; Shu Kondo; Giovanni Bosco (PLoS Genetics)
Drosophila larvae and pupae are at high risk of parasitoid infection in nature. To circumvent parasitic stress, fruit flies have developed various survival strategies, including cellular and behavioral defenses. We show that adult Drosophila females exposed to the parasitic wasps, Leptopilina boulardi, decrease their total egg-lay by deploying at least two strategies: Retention of fully developed follicles reduces the number of eggs laid, while induction of caspase-mediated apoptosis eliminates the vitellogenic follicles. These reproductive defense strategies require both visual and olfactory cues, but not the MB247-positive mushroom body neuronal function, suggesting a novel mode of sensory integration mediates reduced egg-laying in the presence of a parasitoid. We further show that neuropeptide F (NPF) signaling is necessary for both retaining matured follicles and activating apoptosis in vitellogenic follicles. Whereas previous studies have found that gut-derived NPF controls germ stem cell proliferation, we show that sensory-induced changes in germ cell development specifically require brain-derived NPF signaling, which recruits a subset of NPFR-expressing cell-types that control follicle development and retention. Importantly, we found that reduced egg-lay behavior is specific to parasitic wasps that infect the developing Drosophila larvae, but not the pupae. Our findings demonstrate that female fruit flies use multimodal sensory integration and neuroendocrine signaling via NPF to engage in parasite-specific cellular and behavioral survival strategies.